Abordagem etnográfica em avaliação de programas e políticas públicas: um estudo exploratório sobre sua adoção em tribunais de contas brasileiros - Castro, Priscila Lima de (2015)
The aim of this research was to investigate the perception of external auditors of Brazilian state accounts courts on the use of an ethnographic approach in evaluating programs and public policies to contribute to the debate about overcoming restrictive elements to the effectiveness of this approach in the predominant approaches. As a qualitative study of the exploratory type in the depth survey approach, preliminary theoretical and empirical surveys were undertaken to subsidize the establishment of dominant methods analysis categories and the ethnographic approach, as well as the choice of analysis units. Four audit courts chosen by the largest number of public programs and policies evaluations were defined as analysis units, and which counted on the total and exclusive dedication of their teams to these services. Data collection was done through a semi-structured interviews script with two external auditors from each unit, making up eight subjects. Data analysis was performed through content analysis. The results suggest the potential of the ethnographic approach in the evaluation of public policies and programs to improve the understanding of the evaluated context and the best analytical requalification of the numerical conclusions of the evaluations and, above all, the encouragement of social participation and the appropriation of the subject by the communities and citizens in general. On the other hand, they emphasize the possible increase of the immediate costs associated to the traditional approach and the need for training of the auditors in techniques of the ethnographic method. The aforementioned difficulties regarding the adoption of an ethnographic basis technique, however, seem to be relative to the perception shared by the auditors regarding the limitations of the traditional method and the opening of these to the changes and the relative autonomy of the auditors regarding the selection of techniques used in evaluations.